Alternatives Verfahren zur Herstellung von Aluminium - W. Richarz (CHIMIA)
Presently, alumina is industrially produced by the Bayer process and then reduced electrolytically in the Hall-Héroult process. Major disadvantages of the conventional processes are the dependence on bauxite mining countries, loss of sodium hydroxide with the silica content of the bauxite and high energy consumption in the Hall-Héroult-process. The most promising alternative route for the production of aluminium is a process where aluminium chloride is formed and in a subsequent step electrolysed. A direct chlorination with a CO/Cl2 mixture avoids the earlier proposed use of carbon as reducing agent. Results of the measurement of reaction rate for this chlorination of alumina are reported.